Analyzing the Determinants Factors of Dynamic Capability Towards Production Performance: A Case Study of Blacksmith SMEs in Kampar, Riau - Dede Iskandar Siregar; Alum Kusumah; Arista Tri Astuti; Wan Laura Hardilawati (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2023)
Abstract. This study aimed to investigate the relationship between dynamic capability and production performance in manufacturing SMEs. Conceptual models were developed with cost efficiency, quality, flexibility, and speed as outcome variables and dynamic capability as exposure. A sample of 120 respondents was collected using questionnaires, and the data was analyzed using Smart PLS Statistical Software and Structural Equation Modeling. The study's results indicated that dynamic capability significantly impacts product quality, cost efficiency, production flexibility, and production speed. All hypotheses were accepted, highlighting the critical importance of dynamic capability and production performance for manufacturing SMEs, especially in the blacksmith business, where prior research is limited. The study's contribution is significant, as it uniquely integrates dynamic capability, production performance, and manufacturing SMEs. The findings suggest that SMEs can enhance their position for success by improving their dynamic capabilities and production performance. Overall, this study provides valuable insights into the importance of dynamic capability in enhancing production performance for manufacturing SMEs, and its implications can be useful for practitioners, policymakers, and scholars interested in SMEs' growth and competitiveness.Keywords: Dynamic capability, production performance, cost efficiency, quality, flexibility, production speed.Abstrak. Penelitian ini bertujuan untuk menganalisis hubungan antara kemampuan dinamis dan kinerja produksi pada UKM manufaktur. Untuk mencapai tujuan ini, model konseptual telah dikembangkan yang melibatkan variabel hasil seperti efisiensi biaya, kualitas, fleksibilitas, dan kecepatan produksi, serta kemampuan dinamis sebagai faktor eksposur. Sampel diambil dari 120 responden melalui penggunaan kuesioner, dan data dianalisis menggunakan Smart PLS Statistical Software dan Structural Equation Modeling. Temuan penelitian menunjukkan bahwa semua hipotesis telah diterima, yang mengindikasikan bahwa kemampuan dinamis memiliki dampak signifikan pada kualitas produksi, efisiensi biaya, fleksibilitas produksi, dan kecepatan produksi. Penelitian ini menekankan pentingnya kemampuan dinamis dan kinerja produksi pada UKM manufaktur, terutama dalam bisnis pandai besi, di mana penelitian sebelumnya sangat terbatas. Dengan meningkatkan kemampuan dinamis dan kinerja produksi, organisasi UKM dapat memperbaiki posisi mereka untuk mencapai kesuksesan. Pendekatan unik penelitian ini, yang mengintegrasikan kemampuan dinamis, kinerja produksi, dan UKM manufaktur, menegaskan kontribusi unik dari penelitian ini. Oleh karena itu, penelitian ini memberikan kontribusi yang berharga bagi pemahaman kita tentang pentingnya kemampuan dinamis dan kinerja produksi dalam meningkatkan kinerja UKM manufaktur.Kata kunci: Kapabilitas dinamis, kinerja produksi, efisiensi biaya, kualitas, fleksibilitas, kecepatan produksi.